Nectaries in fly-deceptive pitcher-trap blossoms of Aristolochia - Erbar, Claudia; Heiler, Anna; Leins, Peter (Flora, 2017)
The flowers of the eight Aristolochia species studied in this paper (A. arborea, A. clematitis, A. gigantea, A. grandiflora, A. rotunda, A. salvadorensis, A. sempervirens, A. tricaudata) represent three different pollinator deceit cases in this genus: brood site mimic in carrion-fly and fungus-gnat blossoms and food source mimic. In any case, all of them have nectaries on the inner wall of the kettle which provide a small quantity of nectar. As regards the histology, two different types of nectaries can be discerned: the trichomatous type and the so-called nectarioles (termed by Vogel, 1998). The latter type, characterized by clusters of independent and isolated glandular units, is reported for the first time in the kettles of Aristolochia, namely in A. arborea, A. salvadorensis and A. tricaudata. The nectar production in the kettles of the investigated species is regarded as food ensuring survival of the imprisoned pollinators during captivity. Additionally, the location of the nectaries on the inner kettle wall can be interpreted as an adaptation directing the trapped flies to the exit after pollination and fresh pollen loading.